Diffusion of renewable energy technologies: The need for policy in Colombia. (15th September 2016) - Jimenez, Maritza; Franco, Carlos J.; Dyner, Isaac
Abstract: Although the diffusion of solar electricity has been swift worldwide, there is little certainty regarding the adoption of this technology on rooftops, in locations where there is no specific policy on renewables in place. In such cases, there is much uncertainty regarding the effect of solar penetration on electricity prices to consumers and on the reduction of electricity demand from the grid. The penetration of solar in the residential sector – which in some cases accounts for about 40% of the country's total electricity demand – may have a tremendous impact on incumbent utilities and the industry as a whole. Much research has been devoted to assessing the effect of policy on the diffusion of renewables but not much work about the developing world is known, particularly in those nations where institutional arrangements do not favour these technologies. Using system dynamics, this paper examines these issues, considering the diffusion of rooftop solar both with a battery support system, and also without any type of storage system. An important conclusion is that policy is essential for system sustainability when PV diffusion is taking place.